Wave function and dynamic equations to calculet spreading energy of the spin waves in ferromagnetics with spin S=3/2 - رستم, زياد (Latakia University Journal -Basic Sciences Series, 2023)
This reaserch aimed to :1-Finding energy of spin waves distribution in ferromagnetic material with spin S=3/2 starting from finding suitable wave function in chosed graphic kordinate and then the Hameltone and Lagrange and hence the dynamic equations which give concrate descripting of magnons energy levels and his spreading sped. 2– Studying of constant direction and intensity magnetic field and isesotropy (difference properities) on waves distributions energy . 3-Studying the quadra and acto poles that formed on the conserved square of spin . 4-Estimate the earth fundamental situation that the studying system in it, has a minimum ene